From Justice Broker to Village Mediator: Empowering Village Officials in Family Dispute Resolution - Muhamad Nasrudin; Siti Zulaikha; Enny Puji Lestari; Zaini Nasohah; Mufliha Wijayati (Universitas Negeri Semarang, 2025)
This paper reports on community service to shift the role of village officials (pamong desa) from justice brokers to dispute resolution agents. The village civil servants are often used as a reference by disputants when there are family conflicts at the upstream level. Still, sometimes village civil servants make disputants a commodity and living ATM. This service is carried out using the Asset Based Community Development (ABCD) method by presenting a perspective of substantive justice (keadilan hakiki) for women and mubadalah, as well as providing expertise on dispute mediation so that he is able to handle and resolve family disputes earlier. The result is that the village civil servants are very enthusiastic about this empowerment program because they want to maintain the village's reputation and resolve disputes at the village level. Village officials are more gender-sensitive and aware of women's vulnerability as justice seekers. This service succeeded in realizing the importance of peaceful dispute resolution, the basic principles of mediation, and the ability of village officials. This is all beneficial when village officials face family conflicts in the community to act as mediators, not justice brokers. This service initiative further illustrates that the mobilization of community assets constitutes an effective strategy for achieving sustainable problem-solving.